Midterm results of stand-alone thoracoscopic epicardial ablation with box lesion for atrial fibrillation. (23rd June 2021) - Yu, Chunyu; Li, Haojie; Zhang, Heng; Zheng, Zhe
Abstract:  : OBJECTIVES: The short-term results of video-assisted thoracoscopic surgical ablation (VTSA) with box lesion have been highly variable, and the actual efficacy requires clarification through longer follow-ups. We aimed to report which patients might benefit more from VTSA with box lesion by longer follow-up. METHODS: From September 2010 to November 2016, patients with atrial fibrillation (AF) who underwent VTSA with box lesion were screened. All enrolled patients visited the outpatient clinic and underwent 24-h Holter monitoring at 3, 6 and 12 months after surgery and annually thereafter. RESULTS: A total of 91 consecutive patients [age, 58.0 (interquartile interval from 52.0 to 62.0) years; male, 71.4%] with paroxysmal (67%) or persistent/long-standing persistent (33%) AF were enrolled. After a median follow-up of 48 months (interquartile interval from 36 to 60 months), freedom from atrial tachyarrhythmias without antiarrhythmic drugs (AADs) was 76.5%, 66.0% and 66.0% for paroxysmal AF and 58.6%, 47.8% and 34.2% for persistent/long-standing persistent AF at 12, 36 and 60 months, respectively ( P  = 0.017). The preoperative left atrial diameter >40 mm (hazard ratio: 2.837, 95% confidence interval: 1.408–5.716; P  = 0.004) and age >50 years (hazard ratio: 2.927, 95% confidence interval: 1.359–6.305; P  = 0.006) were associated with recurrences of atrial tachyarrhythmias. In patients with paroxysmal AF and left atrial diameter ≤40 mm ( n  = 43), freedom from atrial tachyarrhythmias without AADs was 81.4%, 74.3% and 74.3% at 12, 36 and 60 months, respectively. CONCLUSIONS: In patients with paroxysmal AF and left atrial diameter ≤40 mm, 5-year freedom from atrial tachyarrhythmias without AADs was 74.3%, which was better than that in patients with left atrial diameter >40 mm. A larger sample size and improved study design are needed to confirm our conclusions.